ENVIRONMENTAL ASSESSMENT OF STORMPAV GREEN PAVEMENT FOR STORMWATER MANAGEMENT - Norazlina, Bateni; Nur Sakinah, Mohd Fathil; Rosmina, Ahmad Bustami; Hin Lai, Sai; Mohammad Abdul, Mannan; Darrien Yau Seng, Mah (Penerbit UMT, 2022)
This study evaluates the stormwater management potential of a green pavement technology for permeable road pavement with subsurface micro-detention storage (StormPav) from a water quality perspective. The system provides integration of permeable pavement with hollow spaces to attenuate peak discharge with design installation using precast products. The environmental assessment was gathered from field experiments to assess the water quality, mosquito breeding capability and infiltration rate in the StormPav. The water quality parameters were determined to assess environmental benefits, which are one of the components of sustainable development. The parameters consist of total suspended solids, pH and alkalinity and they showed identical results to other permeable pavement types. Larvae development was found as early as eight days in stagnant water in the cylindrical hollow section of StormPav. However, the StormPav showed a high permeability rate within 122.45 mm/hr to 168.12 mm/hr at subgrade soil of HSG A soils group with no stagnant water retained in the void section in less than two hours, which nullified the required retention time for larvae development. Hence, StormPav displayed a significant benefit in terms of environmental concern for a sustainable design invention in stormwater management with the presence of subsurface detention storage.